A Review Paper on Collaborative Black Hole Attack in MANET (International Journal of Engineering and Computer Science, 2014)
Ad-hoc networks have become a new standard of wireless communication in infrastructure less environment. MANET is a Mobile Ad-hoc Network in which the nodes get connected with each other without an access point. Messages are exchanged and relayed between nodes. Routing algorithms are utilized for forwarding packets between indirect nodes i.e not in direct range with aid of intermediate nodes. They are spontaneous in nature and absence of centralized system makes them susceptible to various attacks. Black hole attack is one such attack in which a malicious node advertises itself as the best route to the destination node and hinders the normal services provided by the network.